Targeting BCL2 in Waldenström macroglobulinemia: from biology to treatment management - Kalafati, Eleni; Kastritis, Efstathios; Bagratuni, Tina (Frontiers in Oncology, 2025)
Despite recent advances in the treatment of Waldenström macroglobulenimia (WM), including the development of Bruton tyrosine kinase inhibitors (BTKis), the disease remains incurable highlighting the urgent need for new treatments. The overexpression of BCL2 in WM cells promotes cell survival by resisting apoptosis and contributes to resistance to chemotherapy and targeted therapies. Concurrently, Bcl2 proteins that are encoded by oncogenes supporting cell survival are frequently upregulated in WM, even in the presence of DNA-damaging agents, and hence have emerged as an alternative therapeutic target. Venetoclax serves as a novel orally administered small agent that targets Bcl-2 protein by acting as a BCL2 homology domain 3 (BH3) mimetic and has shown promising results in WM patients, including those previously treated with BTKis. Furthermore, venetoclax, in combination with standard WM regimens, has shown enhanced activity, but further studies are required to elucidate the mechanism of its synergistic action and identify the patients who can benefit from the combined therapy. New BCL2 inhibitors are in advanced stages of clinical development and may offer additional options. The present review will focus on the current knowledge we have on BCL2 inhibitors in WM, the input of these compounds “from bench to bedside,” and their utility in managing relapsed/refractory WM patients.